2023
DOI: 10.9758/cpn.23.1086
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia and Depressive Disorders

Abstract: Anhedonia is a core symptom of depression and of several psychiatric disorders. Anhedonia has however expanded from its original definition to encompass a spectrum of reward processing deficits that received much interest in the last decades. It is a relevant risk factor for possible suicidal behaviors, and that it may operate as an independent risk factor for suicidality apart from the episode severity. Anhedonia has also been linked to inflammation with a possible reciprocal deleterious effect on depression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Anhedonia is a DA-dependent behaviour and a core feature for depression disorders. In both animal models and depressive patients, the most relevant biological mechanism of anhedonia is the ventral striatal hypoactivation, but dysfunctions in prefrontal cortex also play an important role in abnormal reward processing and impaired reward-related decision making [30]. In addition to changes in behavioural phenotype, our results demonstrated that chronic ACTH injection decreased TH levels in NAcS and ILC.…”
Section: Discussionmentioning
confidence: 71%
“…Anhedonia is a DA-dependent behaviour and a core feature for depression disorders. In both animal models and depressive patients, the most relevant biological mechanism of anhedonia is the ventral striatal hypoactivation, but dysfunctions in prefrontal cortex also play an important role in abnormal reward processing and impaired reward-related decision making [30]. In addition to changes in behavioural phenotype, our results demonstrated that chronic ACTH injection decreased TH levels in NAcS and ILC.…”
Section: Discussionmentioning
confidence: 71%
“…21,22 Both pharmacological and non-pharmacological treatment approaches have been evaluated for treating anhedonia. 23,24 Selective serotonin reuptake inhibitors (SSRIs) are frequently used as first-line agents in the management of MDD. 25,26 They have been shown to have a more pronounced role in reducing the negative affect compared to their role in improving the positive affect or ability of pleasure (ie, improving reward processing and motivation).…”
Section: Introductionmentioning
confidence: 99%
“…Sertraline and fluoxetine, which interact with the dopaminergic system, are reported to be somewhat effective in improving anhedonia. 24 Overall, SSRIs may be of limited clinical utility in the management of anhedonia and amotivation. 12,[26][27][28] A few studies on serotonin-norepinephrine reuptake inhibitors (SNRIs) have reported that they may have a role in improving these symptoms in patients with MDD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations